Enhancing Students’ Speaking Skills with Wordwall Game-Based Learning: Classroom Action Research - Pratiwi, Theodesia Lady; Togatorop, Sarah Ayuandri; Marsevani, Maya (Universitas Lambung Mangkurat, 2024)
The research using the Classroom Action Research (CAR) method aims to help students enhance their speaking abilities through Digital Game-Based Learning (DGBL) using the Wordwall game. This research is motivated by the low speaking skills of students at the elementary level who need innovative methods to increase their participation and speaking ability. This CAR method involves four steps, each consisting of observation, planning, action, and reflection. The findings of this research revealed a considerable improvement in the use of the Wordwall game, including increased active involvement and confidence in speaking. In conclusion, the use of DGBL with Wordwall proved effective in improving the speaking skills of students at the elementary level, as well as creating a more interactive and fun learning environment. This study recommends further use of this method in various educational contexts to improve students’ speaking skills.